Porter Generic Model Strategy for Micro, Small nad Medium Enterprises (MSMs) in Dealing with ASEAN Economic Community (AEC) — )Case Study Deli Serdang Regency, Nort Sumatera — Indonesia) - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Indonesia has entered a new phase with partners in the neighboring countriesm especially ASEAN members, namely ASEAN Economic Community (AEC) on December 31, 2015. One of the main pillars of AEC is free flow of goods, trade in goods in 2015 is conducted Tarifff (CEOT) that hace prevously been appliaed when the ASEAN Free Trade Area (AFTA), namely gradual tarifff reduction made for certain types of goods carried in the timeframe that has been agreed.